2021
DOI: 10.1007/s11739-021-02717-9
|View full text |Cite
|
Sign up to set email alerts
|

Depression and hypertension awareness, treatment, and control in a multiethnic population in the Netherlands: HELIUS study

Abstract: Individuals belonging to ethnic minority groups are more susceptible to depression and comorbid hypertension than European host populations. Yet, data on how depression is related to hypertension in ethnic groups in Europe are lacking. Therefore, we studied the association between significant depressed mood (SDM) and hypertension prevalence, awareness, treatment, and control among ethnic groups. Data from the HELIUS study included 22,165 adults (aged 18–70) from six ethnic backgrounds in the Netherlands. Logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…This is in contrast to several other studies [51][52][53][54][55][56]. However, a recent cross-sectional study in the Netherlands (HELIUS study, n = 21 363) found that hypertension control among depressed people differed between ethnic groups [57]. This supports the importance to understand the association in the Kosovo context, especially given that we observed a much higher prevalence of depression among the Roma, Ashkali, and Egyptian ethnic minority group and poorer hypertension control was observed in ethnic minority groups as seen in the United States [58,59] who might have lower access to healthcare.…”
Section: Depression and Uncontrolled Hypertensioncontrasting
confidence: 66%
“…This is in contrast to several other studies [51][52][53][54][55][56]. However, a recent cross-sectional study in the Netherlands (HELIUS study, n = 21 363) found that hypertension control among depressed people differed between ethnic groups [57]. This supports the importance to understand the association in the Kosovo context, especially given that we observed a much higher prevalence of depression among the Roma, Ashkali, and Egyptian ethnic minority group and poorer hypertension control was observed in ethnic minority groups as seen in the United States [58,59] who might have lower access to healthcare.…”
Section: Depression and Uncontrolled Hypertensioncontrasting
confidence: 66%
“…The underlying mechanisms between depression or anxiety and hypertensive crisis are that the stress response precipitated by depression leads to overactivity of the nervous system and the hypothalamic-pituitary-adrenal axis, promoting the sequelae of hypertension [ 26 ]. Other factors attributing to their correlation include poor adherence to antihypertensives in clinically depressed individuals, lack of physical activity, and use of antidepressant drugs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms between depression or anxiety and hypertensive crisis are that the stress response precipitated by depression leads to overactivity of the nervous system and the hypothalamic-pituitary-adrenal axis, promoting the sequelae of hypertension [ 26 ]. Other factors attributing to their correlation include poor adherence to antihypertensives in clinically depressed individuals, lack of physical activity, and use of antidepressant drugs [ 26 ]. Anxiety is also known to activate the sympathetic nervous system as a stress response mechanism, leading to the release of neurotransmitters that cause tachycardia, increased inotropism, and vasoconstriction, ultimately impacting blood pressure levels [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that greater depressive symptoms was associated with great hypertension awareness and treatment but not with control may be associated with several factors associated with either hypertension or depression, including healthcare system use, other coexisting conditions and adherence to treatment [37][38][39][40]. In addition, a recent report from the Netherlands showed significant differences in the association between depression and hypertension awareness, treatment and control between ethnic groups [39], suggesting that further study to assess the ethnicity-related factors affecting the association between depression status and hypertension is needed among diversity population.…”
Section: Discussionmentioning
confidence: 99%